AKHLAK SISWA DI MAL UIN SU MEDAN - Ramadhani Hasibuan (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2017)
Abstrak: The purpose of this research is to find out the correlation between learning source to learningresult of Islamic education in MAl UIN SU. To know the relationship of learning motivation to thelearning result of Islamic education in SMP Negeri 3 Binjai. And to know the relationship betweenlearning resources and motivation to learn simultaneously with the learning result of Islamic educationin MAl UIN SU. The research method used is quantitative method, that is research with level of variationmore complex, so require statistical analysis. The analysis is conducted on the variables studied, and alsothe relationship between these variables. With data collection techniques using, document studies, questionnairesand observations. The population in this study is all students of MAl UIN SU In the 2016/2017academic year that is Muslim, which amounts to 1297 people consisting of 39 classes. And the number ofsamples is 78 students taken 2 (two) students (one male and one female) in each class by drawing the listof names in absent.Penelitian ini bertujuan untuk mengetahui bagaimana problema pembinaan akhlak siswa di tinjau darisudut guru, siswa dan lingkungan sekolah. Dan Untuk mengetahui pembinaan siswa melalui berbagaiaktifitas belajar baik intrakurikuler maupun ekstrakurikuler. Serta Untuk mengetahui bagaimana faktorpendukung dan penghambat dalam pembinaan akhlak siswa di MAL UIN SU Medan. Metode Penelitianini adalah penelitian lapangan (Field research) yaitu peneliti melakukan penelitian langsung ke lokasiuntuk mendapatkan dan mengumpulkan data. Penelitian yang dilaksanakan di lapangan adalah menelitimasalah yang sifatnya kualitatif, yakni prosedur data penelitian yang menghasilkan data deskriptifberupa kata-kata yang tertulis atau lisan dari orang-orang dan perilaku yang diamati.1 Sehingga dapatdikatakan bahwa penelitian ini bersifat deskriptif kualitatif. Artinya, peneliti menganalisis dan menggambarkanpenelitian secara objektif dan mendetail untuk mendapatkan hasil yang akurat.Kata Kunci:Akhlak Siswa